Al-Mawardi’s Leadership Concept and Its Relevance to Indonesian Democracy - Kharisma Elok; Hafizd, Jefik; Mohamad Rana (Journal of Law Justice (JLJ), 2025)
This study analyzes Al-Mawardi’s concept of leadership as presented in Al-Ahkam al-Sultaniyyah and evaluates its relevance to Indonesia’s democratic system. Al-Mawardi emphasizes that a leader must possess justice, wisdom, courage, and a strong sense of responsibility in carrying out leadership duties. He also highlights the importance of law enforcement, public welfare, and the appointment of competent officials as the foundation of a stable government. This research employs a library research method with a qualitative descriptive approach. The primary source is Al-Mawardi’s work, analyzed alongside relevant literature on fiqh siyasah and Indonesia’s governance system. The findings indicate that several of Al-Mawardi’s leadership principles, such as justice, public welfare, and the supremacy of law, align with the values of Pancasila and the principles of democracy in Indonesia. However, fundamental differences exist in the selection mechanism of leaders, the authority of institutions involved, and the process of dismissing a head of state. Al-Mawardi’s concept prioritizes legitimacy based on religious and individual expertise, whereas Indonesia’s democratic system emphasizes public participation and structured institutions. In conclusion, Al-Mawardi’s thoughts remain relevant as a conceptual reference for developing leadership that upholds justice and prioritizes public interest. However, their application in a modern democratic system requires reinterpretation to align with Indonesia’s evolving political and legal dynamics.